Certain Geometric Properties of Normalized Wright Functions - Mohsan Raza; Muhey U Din; Sarfraz Nawaz Malik (Journal of Function Spaces)
In this article, we find some geometric properties like starlikeness, convexity of order α, close-to-convexity of order 1+α/2, and close-to-convexity of normalized Wright functions with respect to the certain functions. The sufficient conditions for the normalized Wright functions belonging to the classes Tγα and Lγα are the part of our investigations. We also obtain the conditions on normalized Wright function to belong to the Hardy space Hp.